2009
DOI: 10.1002/da.20564
|View full text |Cite
|
Sign up to set email alerts
|

Broad spectrum of cytokine abnormalities in panic disorder and posttraumatic stress disorder

Abstract: These findings suggest that a generalized inflammatory state may be present in individuals with PD or PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
239
9
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(270 citation statements)
references
References 61 publications
(76 reference statements)
17
239
9
5
Order By: Relevance
“…It should be noted that similar changes in immune parameters including increases in inflammatory markers have also been described in patients with a variety of psychiatric disorders other than depression including bipolar mood disorders and anxiety disorders as well as schizophrenia (Konuk et al, 2007;Hoge et al, 2009;Pace and Heim, 2011;. Moreover, what has become increasingly clear is that none of these disorders, including notably major depression, are fundamentally inflammatory disorders, but rather in each case, there is a subgroup of patients who exhibit evidence of increased inflammation (Raison and Miller, 2011).…”
Section: Foundations For the Hypothesis That The Immune System Plays mentioning
confidence: 82%
“…It should be noted that similar changes in immune parameters including increases in inflammatory markers have also been described in patients with a variety of psychiatric disorders other than depression including bipolar mood disorders and anxiety disorders as well as schizophrenia (Konuk et al, 2007;Hoge et al, 2009;Pace and Heim, 2011;. Moreover, what has become increasingly clear is that none of these disorders, including notably major depression, are fundamentally inflammatory disorders, but rather in each case, there is a subgroup of patients who exhibit evidence of increased inflammation (Raison and Miller, 2011).…”
Section: Foundations For the Hypothesis That The Immune System Plays mentioning
confidence: 82%
“…The current literature provides accruing evidence for excessive peripheral inflammation in PTSD. Evaluation of basal or stimulated peripheral cytokines (Maes et al, 1999;Spivak et al, 1997;Wong et al, 2000;Bob et al, 2010;Gill et al, 2010;Hoge et al, 2009;Symes et al, 2010;Tucker et al, 2010;von Känel et al, 2010;Lindqvist et al, 2014;Tursich et al, 2014;Plantinga et al, 2013) indicates there are abnormally increased concentrations of proinflammatory cytokines in patients with PTSD in most, but not all studies (de Kloet et al, 2007;Miller et al, 2001;Song et al, 1999). Few studies have examined cytokine levels in the CSF of individuals with PTSD.…”
Section: Inflammation and Ptsdmentioning
confidence: 99%
“…Extensive research has shown that chronic neuroinflammation continues for months to years after injury, [9][10][11][12] and evidence for chronic inflammation has been observed in a number of studies examining patients with PTSD, panic disorder, obsessive-compulsive disorder (OCD), and generalized anxiety disorder. [13][14][15][16][17][18] Glial activation may be involved in the development and maintenance of PTSD, [9][10][11][12] and mounting evidence supports the role of inflammatory processes in both TBI and anxiety disorders. After injury, immune cells rapidly produce endogenous danger signals or ''alarmins,'' which function as potent effectors of innate defense and promote immune system activation by recruiting antigen-presenting cells (APCs) that relay and amplify the inflammatory response.…”
mentioning
confidence: 99%
“…9,27,90 Chronic inflammation has been observed in a number of studies examining patients with trauma-related anxiety disorders, reporting increases in downstream mediators, such as peripheral elevations of TNF-a, interferon-gamma (IFN-c), IL-1b, and IL-6, in patients with PTSD, [13][14][15][16] elevations of TNF-a and IL-6 in patients with OCD, 17 and elevations in proinflammatory cytokines and chemokines (monocyte chemoattractant protein 1, macrophage inflammatory protein 1 alpha, IL-1a, IL-1b, IL-6, IL-8, Eotaxin, granulocyte macrophage colony-stimulating factor, and IFN-c) in individuals with panic disorder and PTSD. 18 Despite compelling evidence implicating excessive inflammatory actions and a generalized inflammatory state in the development of anxiety disorders after TBI, central measures of proinflammatory cytokine elevations specifically related to human PTSD and other anxiety disorders have not yet been performed. However, the current results provide evidence for chronic neuroinflammation in the development and maintenance of post-traumatic anxiety in an animal model, as indicated by elevated immunoreactivity in the amygdala and insula at 6 months postinjury.…”
mentioning
confidence: 99%